2015
DOI: 10.1002/j.2334-5837.2015.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

“Suits you sir! ‐‐ choosing the right style of SE before tailoring to fit”

Abstract: Despite significant evidence that Systems Engineering (SE) adds value, take‐up is patchy. There is a growing volume of evidence that the ‘understand‐plan‐do’ paradigm behind conventional Systems Engineering only works in some circumstances. We have seen situations where SE has either over‐complicated the solution or was unable to deliver quickly enough. Applying SE in these situations leads to both a specific failure and damages the credibility of SE more broadly. This paper: Proposes a new, two phase, tailor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The first step in Kotter's 8 step change process (Kotter, 1995) is creating a sense of urgency to drive a change in the organization. As discussed in (Kemp, Beasley, & Williams, 2015) the key first stage is to tailor the Systems Engineering to the organization's needs. Table 1 includes a range of potential organisational needs that the authors have used SE to help solve.…”
Section: Making and Sustaining The Case For Sementioning
confidence: 99%
See 1 more Smart Citation
“…The first step in Kotter's 8 step change process (Kotter, 1995) is creating a sense of urgency to drive a change in the organization. As discussed in (Kemp, Beasley, & Williams, 2015) the key first stage is to tailor the Systems Engineering to the organization's needs. Table 1 includes a range of potential organisational needs that the authors have used SE to help solve.…”
Section: Making and Sustaining The Case For Sementioning
confidence: 99%
“…Not all organizational cultures support the need for systems engineering process based "… on defining customer needs and required functionality early in the development cycle, documenting requirements, then proceeding with design synthesis and system validation while considering the complete problem" (INCOSE, 2018) (Snowden & Boone, 2007) describes the Cynefin framework (Figure ), which describes the different management styles needed to deal with radically different situations. (Cowper, Kemp, Elphick, & Evans, 2014) and (Kemp, Beasley, & Williams, 2015) describe how Systems Engineering operates in the Complicated (and occasionally Complex) spaces. Finally, (Obeng, 1995) identifies a series of project types (Figure 3), with different approaches based upon the level of certainty in approach and outcome.…”
Section: Deciding What Delivery Culture Is Requiredmentioning
confidence: 99%
“…Currently, many systems engineers talk about "the" systems engineering process. Kemp et al (2015) assert that the currently dominant systems engineering process model is suitable mainly for large one-of-a-kind solutions to complicated problems, and needs to be substantially modified to deal with complex, simple, and chaotic systems and situations. We agree with this analysis, and envisage that families of systems engineering process models will be developed to cope with multiple dimensions of variation, of which we discuss three.…”
Section: Four Aspects Of Systems Engineeringmentioning
confidence: 99%
“…Whilst the tube map depicts a linear, "left-to-right" process, the guidance now includes set of principles to inform any tailoring that might be needed to suit the needs of the programme and its constituent projects (including the potential for incremental or agile approaches). This has been kept deliberately high level, and uses the Cynefin framework (Snowden & Boone 2007) shown in Figure 10, augmented by the findings presented in (Cowper et al 2014) and (Kemp et al 2015), and Obeng's "types of project" model (Obeng 1995), shown in Figure 11, to inform any decisions about fine-tuning the scope and scale-of-effort for each activity.…”
Section: Figure 9 -Relationship Between Benefits Requirements and Camentioning
confidence: 99%